THE INFLUENCE OF E-WALLET USAGE AND CONSUMER KNOWLEDGE ON PURCHASING DECISIONS AT SHOPEE ON GEN Y IN THE MESTIKA MANDALA COMPLEX MEDAN - Jocelyn Jovita; Ihdina Gustina (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
Shopee is an e-commerce platform that was launched in 2015 and has become one of the leading marketplaces in Southeast Asia and Taiwan. Known for its user-friendly interface, Shopee provides a variety of products ranging from fashion to electronics. This study aims to determine the effect of E-wallet Usage and Consumer Knowledge on Purchasing Decisions at Shopee on Gen Y in the Mestika Mandala Medan Complex. With the increasing popularity of E-wallets as a digital payment method, especially among Generation Y, knowledge and proper use can influence their shopping behavior. The research method used is a quantitative method involving respondents from Generation Y who actively use Shopee with the population in this study being the entire Generation Y in the Mestika Mandala Medan Complex. The sample was obtained using the Hair et al formula. So that 120 respondents were obtained. The research instrument used a questionnaire with a Likert measurement scale. The results showed that the use of E-wallets, which includes convenience, security, and transaction speed, has a significant positive impact on Purchasing Decisions. In addition, high consumer knowledge about the features and benefits of E-wallets also contributes to increasing user trust and buying interest and has a positive and significant effect on Purchasing Decisions.